Virtual Tour Application Of Natural Tourism In Bandar Lampung City Based On Android - Mali Fakhrurrozi; Yuni Puspita Sari (Proceeding International Conference on Information Technology and Business, 2019)
Bandar Lampung is the capital of Lampung province on the island of Sumatra, Indonesia. Bandar Lampung has a variety of natural attractions such as beaches, hills, zoos and others. Natural attractions in Bandar Lampung include Wira Garden Tourism Park, Lembah Hijau and Bumi Kedaton. The three tourist attractions have a very large land and a lot of rides. The problem happens is that the visitors can not enjoy all the rides that exist, one of which is due to the limited information provided by the tourist attraction objects. The method used in this study was the Prototype method. The software used in building this application was the Android Studio with the java programming language, and phpMyAdmin as the database server. Virtual tour of natural tourism applications in the city of Bandar Lampung based on Android provides information to visitors in the form of complete information about rides, 3600 panoramic photos of rides and the location of tourist attractions connected with Google maps.Key Words :Panorama 3600,android studio ,prototype, googlemaps